Integration of IoT and Smart Sensor Technology for Multi-Parameter Monitoring of Seawater Quality - Handy I.R. Mosey; Andi Ikhtiar Bakti; Maria D. Bobanto; Mans L. Mananohas (JURNAL PESISIR DAN LAUT TROPIS, 2025)
This study designs and implements a portable water quality measuring device as an alternative solution for monitoring the physical parameters of seawater. The system is developed to measure sea surface temperature, Total Dissolved Solids (TDS), and electrical conductivity (EC). It employs a Keystone TDS v1.0 sensor and a DS18B20 temperature sensor. A NodeMCU V3 microcontroller module equipped with Wi-Fi is used as the data processor for sensor readings and as the data transmitter to the internet via a modem. The measurement data are transmitted wirelessly and displayed through the Internet of Things (IoT) applications Blynk and Telegram. Device calibration was carried out using a comparative method compared to standard instruments at the Basic Physics Laboratory, Faculty of Mathematics and Natural Sciences, Sam Ratulangi University (FMIPA-UNSRAT). Performance testing was conducted in the Manado Reclamation Coastal Area on October 17, 2025. The sensor measurement data were validated using the Root Mean Square Error (RMSE) method to evaluate sensor accuracy, yielding an RMSE value of 1.887 with a standard deviation of 0.295. The validation results indicate that the sensor’s data reading accuracy is considerably high. Keywords: water quality, physical parameter, internet of things, sensor   Abstrak Penelitian ini merancang dan mengimplementasikan perangkat pengukur kualitas air portabel sebagai solusi alternatif untuk pemantauan parameter fisika air laut. Sistem dirancang untuk memantau suhu permukaan, Total Dissolved Solid (TDS), dan konduktivitas Listrik. Sistem ini dirancang dengan menggunakan sensor TDS v1.0 dari keystone dan sensor suhu DS18B20.  Modul mikrokontroler NodeMCU V3 yang telah dilengkapi WiFi digunakan sebagai pemroses data pembacaan sensor dan sebagai pengirim data pengukuran ke jaringan internet melalui modem.  Data hasil pengukuran dikirim secara nirkabel selanjutnya ditampilkan melalui aplikasi Internet of Things (IoT) Blynk dan aplikasi Telegram. Kalibrasi perangkat dilakukan dengan metode komparatif terhadap alat standar pada Laboratorium Fisika Dasar FMIPA-UNSRAT. Uji performa perangkat dilaksanakan di Kawasan Reklamasi Pantai Manao pada 17 Oktober 2025. Data hasil pengukuran sensor divalidasi dengan menggunakan metode Root Mean Square Error (RMSE) untuk mengukur tingkat akurasi sensor, dengan nilai sebesar RMSE sebesar 1,887 dengan standar deviasi sebesar 0,295. Hasil validasi menunjukkan bahwa akurasi pembacaan data sensor sangat tinggi. Kata kunci: kualitas air, parameter fisika air, internet of things, sensor.